Traktat lizboński i jego implikacje dla francusko-niemieckiej współpracy w obszarze Wspólnej Polityki Bezpieczeństwa i Obrony Unii Europejskiej - Anna Paterek (Ksiegarnia Akademicka Publishing, 2019)
The Lisbon Treaty and Its Implications for French‑German Cooperation in EU’s Common Security and Defence Policy Faced with internal and external pressures the EU’s security and defence policy has become one of the most dynamic fields of European integration. This paper describes declared ambition of Franco‑German cooperation to strengthening the EU in European security and defence. In light of a more demanding security environment Berlin and Paris have awakened the so‑called „Sleeping Beauty of the Lisbon Treaty”, The Permanent Structured Cooperation (PESCO), introduced by the 2009 Lisbon Treaty. They managed to find a compromise and to turn PESCO into a process as much as to create a new framework to deepen defence cooperation amongst EU Member States. The conclusions argue that the relaunch of the Franco‑German motor is key to European defence.